Hubungan Konflik Tokoh Dengan Politik Dan Teori Konspirasi Dalam Film “Mencuri Raden Saleh” - Nur Fadilah, Malika; Sodiq, Syamsul (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
The main problem raised in this study is about the relationship between the character's conflict with politics and conspiracy theories in the film "Mencuri Raden Saleh". As for the goal is to reveal a picture of the relationship between the conflict figures with politics and conspiracy theories. The method used is to use the method of literature and note-taking techniques. In the data analysis method used descriptive qualitative method. The result of the research is the alleged relationship between political figures and conspiracy theories such as 1). The reasons why Piko's father stole the painting of Prince Diponegoro's arrest, 2). Regarding Rama, the son of Permadi who is always protected, and 3). Ucup is a DPO (wanted list). Apart from that, there was another conflict between Ucup and Gofar which was triggered by a misunderstanding between the two. So it can be concluded that in this film there are indeed various conspiracy theories and character conflicts that are triggered by existing problems.